Treatment Patterns, Toxicity, and Outcomes of Older Adults With Advanced Pancreatic Cancer Receiving First-line Palliative Chemotherapy. (February 2022) - McAndrew, Erin N.; Zhang, Hanbo; Lambert, Pascal; Rittberg, Rebekah; Dawe, David E.; Kim, Christina A.
Abstract : Objectives: Advanced pancreatic cancer (APC) disproportionately impacts older adults. Randomized trials demonstrate improved overall survival (OS) with combination chemotherapy including 5-fluorouracil, irinotecan, leucovorin, and oxaliplatin (FOLFIRINOX) or nab -paclitaxel and gemcitabine compared with gemcitabine alone, but with increased toxicity. Older adults are at increased risk of side effects from chemotherapy. The aim of this study was to assess the efficacy and toxicity of chemotherapy in older adults with APC. Methods: Patients diagnosed with APC from 2011 to 2016 were identified using the Manitoba Cancer Registry. Patient and treatment characteristics, toxicity, and outcomes of patients 65 years of age and above treated with palliative chemotherapy were compared by treatment regimen. OS was assessed using the Kaplan-Meier method. A Cox regression was used to identify independent predictors of OS. Results: A total of 87 patients aged 65 years and above received palliative chemotherapy: 52 (59.7%) FOLFIRINOX, 21 (24.1%) nab -paclitaxel and gemcitabine, and 14 (16.1%) gemcitabine, with a median age of 69 (65 to 84), 75 (65 to 88), and 73 (67 to 82), Eastern Cooperative Oncology Group (ECOG) performance status difference in hematologic toxicity between regimens ( P =0.807). An increase in nonhematologic toxicity was seen with FOLFIRINOX ( P <0.001), specifically neuropathy ( P =0.008), fatigue ( P <0.001), and nausea/vomiting ( P =0.008). FOLFIRINOX was associated with improved radiologic response ( P =0.05) and OS ( P =0.035). PS, baseline carbohydrate antigen 19-9 level, and chemotherapy regimen were independent predictors of survival. Conclusions: FOLFIRINOX is associated with improved response and OS in older adults with APC. FOLFIRINOX has a manageable safety profile in this population and should be considered in fit older adults with APC.